Science Policy, "Strategic" Research, and Journal Papers: Exploring Their Influence on the History of the Rowett Research Institute. - Watts, David (Centaurus: Journal of the European Society for the History of Science, 2024)
This paper makes two claims to originality. First, it responds to a recent call for more studies into how research institutions built resilience to changes in science policy and funding in Britain, by examining the history of the Rowett Research Institute, a nutrition science institute established in the 1910s in north-east Scotland. The discussion starts by reviewing the historiography of British science policy since the early 20th century, focusing particularly on agricultural science, the policy arena within which the Rowett developed. The second claim to originality stems from the paper's use of quantitative evidence. It draws on the historiography of scientific journal papers to argue for their utility as a source of data on research conducted at the Rowett, and potentially elsewhere. These "bibliometric" data, along with figures on staff numbers and research income, are used to triangulate the qualitative archival and historiographical data, allowing the Institute's resilience to be examined over a considerable period including, but not restricted to, occasions when science policy changed significantly. Using these quantitative and qualitative data allows this paper to demonstrate how, over a century of scientific work, funded primarily by the government to undertake "strategic" and "applied" research, Rowett scientists negotiated the tension between getting papers published in scientific journals and providing "applied" benefits for users. In doing so, it provides further evidence for the artificiality of the distinction, which has long influenced science policy in Britain, between "pure" and "applied" research. Trends in the production of scientific journal papers by Rowett scientists resemble those in science more generally and show that they have always been members of the "invisible colleges" of their respective disciplines.